A method for producing an optical base film for a polarizing plate having high microflatness
Patent Information
- Application Number
- CN202310827908.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-30
- Filing Date
- 2023-07-07
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-07-07
AI Technical Summary
[0004]本发明要解决的技术问题是提供一种高微观平整性的偏光片用光学基膜的制备方法,能够解决现有技术中光学基膜表面会出现“橘皮”状微观不平整现象、团聚凸出的开口剂粒子会对胶层表面平整性造成明显影响导致偏光片贴合玻璃基板时出现光斑等瑕疵的问题
[0014]本发明的优点在于:采用对聚酯具有亲和性的片状粒子作为开口剂,开口剂在进入挤出系统后,通过特殊设计的熔体挤出设备,使其受到的水平剪切力大为提高,开口剂片状粒子水平均匀分散在呈层流状态的聚酯熔体中,通过三层挤出后水平排列在薄膜表面,通过制备工艺的改进,制备出的偏光片用光学基膜在满足粗糙度Ra值≤50nm,Rmax≤600nm的前提下,膜面微观无橘皮纹路,开口剂片状粒子均匀排布且无尺寸≥50μm、高≥5μm的团聚物,开口剂片状粒子与聚酯基材亲和性好,分散均匀,团聚少且凸出膜面程度低,成品微观平整性极佳;
Smart Images

Figure CN118404828B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyester film preparation technology, and specifically to a method for preparing an optical base film for polarizers with high microscopic flatness. Background Technology
[0002] With the rapid development of the display panel industry and its shift to China, the demand for liquid crystal displays (LCDs) is increasing daily, and polarizers are a key component of LCDs. The optical base film used in polarizers is polyethylene terephthalate (PET) film. Polarizer production involves various types of process protection films and structural protection films, such as release films, protective films, and PVA film protective films. The release film base film protects the PSA adhesive layer of the polarizer. Therefore, the "orange peel" micro-unevenness and agglomerated protruding opening agent particles on the surface of the base film will significantly affect the smoothness of the adhesive layer surface, leading to defects such as light spots when the polarizer is bonded to the glass substrate. To solve this problem, in addition to using opening agent particles with good affinity to the polyester substrate and improving the dispersion uniformity of the opening agent particles in the high-temperature polyester melt to reduce particle agglomeration, it is also necessary to ensure that the opening agent is arranged as flatly and regularly as possible on the film surface to solve the critical defect of "orange peel."
[0003] In the prior art, CN1283211A discloses a "low-haze, spotless polyester film," which uses calcined porous organosilicon particles as opening agents. The porous structure can further enhance the adhesion between the particles and the polyester, and control the particle size to below 7 μm, thereby preventing agglomeration. However, the particle size distribution of the opening agents in this film is too wide, which is not conducive to controlling the surface micro-smoothness. CN201380045267.6 discloses a "polyester resin composition and polyester film using the composition," which uses silica particles coated with metal compounds as opening agents, thereby preventing internal defects caused by particle agglomeration and achieving improved film surface properties, low haze, and improved transparency, thus making the polyester resin composition suitable as a substrate film for optical films and electronic materials. However, no effective method for improving "orange peel" defects is described. CN110720062 A discloses an "optical body comprising a multilayer optical film and a thin adhesive layer," which uses a method of attaching a continuous adhesive layer to the surface of the thin film to reduce the incidence and severity of uneven "orange peel" defects. However, this method requires the application of multiple adhesive layers, significantly increasing costs and inevitably introducing uncertainties into existing polarizer manufacturing processes. This invention provides a method for preparing a polarizer optical base film with high microscopic flatness. The prepared high-flatness polarizer optical base film can be applied to polarizer manufacturing process protection materials and structural materials, including but not limited to polarizer release film base film, polarizer protective film base film, and polarizer PVA film protective film. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing an optical base film for polarizers with high microscopic flatness, which can solve the problems in the prior art where the surface of the optical base film has an "orange peel" microscopic unevenness, and the agglomerated protruding opening agent particles have a significant impact on the surface flatness of the adhesive layer, resulting in defects such as light spots when the polarizer is bonded to the glass substrate.
[0005] To solve the above-mentioned technical problems, the technical solution of the present invention includes the following steps: S1. Extrusion: Polyester chips are extruded into shape using a melt extrusion device. The polyester chips are melted in the main melt chamber and auxiliary melt chamber of the melt extrusion device, and then flow out precisely and compounded through a filter and melt pipe at the die distribution block. The extrusion temperature is 250~295℃. In order to increase the transverse shear force of the sheet particles at the laminar flow element in the melt pipe, the temperature of the melt pipe is set to at least two temperature sections, including the temperature before the laminar flow element and the temperature at the laminar flow element. The temperature before the laminar flow element is higher, and the temperature at the laminar flow element is lower than the melting temperature. From the laminar flow element to the laminar flow element, the temperature is set to 270~285℃ and 250~270℃, respectively. After passing through the laminar flow element, the melt enters the die, and the temperature of the die is raised above the melting point. The die temperature is set to 275~290℃. S2, Casting: The melt flows through the die lip to the casting roll to form a casting sheet; S3. Longitudinal stretching: The casting sheet is stretched longitudinally. S4. Lateral stretching: The sheet that has been stretched longitudinally is then stretched laterally. The polyester chips include polyester masterbatch and polyester base material. The polyester masterbatch includes open-opening agent flake particles with affinity for polyester and PET. The polyester masterbatch is prepared by co-extrusion granulation of open-opening agent flake particles with affinity for polyester and PET. The opening agent flake particles are one or a combination of several of the following: flake calcium aluminate, graphene oxide, reduced graphene oxide, silane graphene, and TiO2 / graphene composite. The length and width of the opening agent flake particles are 100~5000nm, and the thickness is 10~500nm. The proportion of the opening agent flake particles in the polyester masterbatch is 100~10000ppm; The amount of polyester masterbatch added is 1% to 20% of the total amount of polyester chips.
[0006] Furthermore, the opening agent flake particles are one or a combination of several of reduced graphene oxide, silane graphene, and TiO2 / graphene composite; the length and width dimensions of the opening agent flake particles are 500~3000nm, and the thickness is 10~200nm; the proportion of the opening agent flake particles in the polyester masterbatch is 1000~10000ppm. In step S1, the temperatures from the laminar flow element to the laminar flow element are set to 270~280℃ and 250~265℃ respectively; the die head temperature is set to 275~285℃. The amount of polyester masterbatch added is 3% to 15% of the total amount of polyester chips.
[0007] Furthermore, the length and width of the opening agent flake particles are 1000~2000nm, and the thickness is 10~50nm; the proportion of the opening agent flake particles in the polyester masterbatch is 3000~5000ppm; In step S1, the temperatures from the laminar flow element to the laminar flow element are set to 270℃~275℃ and 260~265℃ respectively; the die head temperature is set to 280~285℃. The amount of polyester masterbatch added is 5% to 10% of the total amount of polyester chips.
[0008] Furthermore, in step S2, the temperature of the casting roll is 30~40℃, the distance between the die lip and the contact position of the casting roll is 2.5~5mm, and the shrinkage of the casting width is 3~6%.
[0009] Furthermore, in step S3, during longitudinal stretching, the temperature of the preheating roller is 75~95℃, the temperature of the stretching roller is 85~100℃, and after preheating, longitudinal stretching is performed with a longitudinal stretching ratio of 2.5~4 times. Then, cooling is performed with a cooling roller temperature of 20~40℃.
[0010] Further, in step S4, during the transverse stretching, the preheating temperature is 100~130℃, the transverse stretching temperature is 120~145℃, the transverse stretching after preheating takes 5~15s, the transverse stretching ratio is 3.5~5 times, the high-temperature setting temperature is 200~240℃, the high-temperature setting time is 12~25s, the low-temperature setting temperature is 100℃~175℃, the low-temperature setting time is 5~10s, and after heat setting, the cooling temperature is 30~50℃, and the cooling time is 5~10s.
[0011] Further, in step S1, the melt extrusion equipment has a feeding channel and an extruder. The feeding channel is located at the feed inlet of the extruder. The extruder includes a melting chamber, a metering pump, a melt pump, a filter, a melt pipeline, and a die. The melting chamber is connected to the metering pump. The metering pump is connected to the melt pump. A discharge valve is provided between the melt pump and the filter. The outlet end of the filter is connected to the inside of the melt pipeline. The melt pipe has a pipe wall and a laminar flow element. The laminar flow element is located inside the melt pipe and is positioned near the outlet end of the melt pipe. The laminar flow element has three plate-shaped structural members arranged in parallel vertically. The three plate-shaped structural members are horizontally arranged and evenly spaced. The two sides of the plate-shaped structural members are welded to the pipe wall. The outlet end of the melt pipe is connected to the die head. The process of producing optical base film by melt extrusion of polyester chips using the melt extrusion equipment is as follows: The mixed polyester masterbatch and polyester base material are fed into the melt chamber of the extruder through the feeding channel for melting and plasticization. The raw materials are accurately metered and transported by the metering pump and then further propelled forward by the melt pump. The raw materials enter the filter through the discharge valve. After the filter removes impurities from the raw material melt, the melt enters the melt pipe. When passing through the laminar flow element in the latter half of the melt pipe, the opening agent flake particles are encapsulated in the polyester masterbatch. As the melt passes through the laminar flow element, it is subjected to strong parallel shear force under a specific temperature gradient. The opening agent flake particles stack along the thickness direction and are arranged horizontally layer by layer along the direction of travel. Then, it enters the die head and is extruded and formed. The opening agent flake particles are neatly arranged horizontally in the melt, thus forming a horizontal arrangement on the surface of the optical base film, resulting in high surface smoothness of the optical base film.
[0012] Furthermore, the roughness Ra value of the pipe wall is 10~1000nm to promote melt flow; the roughness Ra value of the laminar flow element is 100~2000nm.
[0013] Furthermore, the roughness Ra value of the pipe wall is 10~100nm; the roughness Ra value of the laminar flow element is 100~500nm.
[0014] The advantages of this invention are as follows: It uses flake-like particles with affinity for polyester as the opening agent. After entering the extrusion system, the opening agent is subjected to significantly increased horizontal shear force through a specially designed melt extrusion device. The flake-like particles of the opening agent are horizontally and uniformly dispersed in the polyester melt in a laminar flow state. After three-layer extrusion, they are horizontally arranged on the film surface. Through the improvement of the preparation process, the optical base film for polarizing films prepared meets the requirements of roughness Ra value ≤ 50nm and Rmax ≤ 600nm. The film surface is free of orange peel texture, the flake-like particles of the opening agent are uniformly arranged and there are no agglomerates with a size ≥ 50μm and a height ≥ 5μm. The flake-like particles of the opening agent have good affinity with the polyester substrate, are uniformly dispersed, have few agglomerates, and have a low degree of protrusion from the film surface, resulting in excellent microscopic smoothness of the finished product. Using specific opening agent flake particles, only a small amount is needed to achieve excellent results; The specially designed melt extrusion equipment has a simple structure and is highly practical; The preparation process of the optical base film for polarizers provided by this invention is simple and highly feasible. Attached Figure Description
[0015] Figure 1 This is a schematic diagram of the melt extrusion equipment of the present invention.
[0016] Figure 2 This is a cross-sectional view of the melt pipe of the melt extrusion apparatus of the present invention.
[0017] Figure 3 This is a side view of the melt pipe of the melt extrusion apparatus of the present invention. Implementation
[0018] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. The following embodiments will enable those skilled in the art to more fully understand this invention, but do not limit the invention to the scope of these embodiments.
[0019] This specific implementation method adopts the following technical solution, including the following steps: S1. Extrusion: Polyester chips are extruded into shape using a melt extrusion device. The polyester chips are melted in the main melt chamber and auxiliary melt chamber of the melt extrusion device, passed through a filter and melt pipe, and then precisely compounded and flowed out at the die distribution block. The extrusion temperature is 250~295℃. In order to increase the transverse shear force of the sheet particles at the laminar flow element in the melt pipe, the temperature of the melt pipe is set to at least two temperature segments, including the temperature before the laminar flow element and the temperature at the laminar flow element. The temperature before the laminar flow element is higher, and the temperature at the laminar flow element is lower than the melting temperature. From the laminar flow element to the laminar flow element, the temperatures are set to 270~285℃ and 250~270℃, respectively. Preferably, the temperatures from the laminar flow element to the laminar flow element are set to 270~280℃ and 250~265℃, respectively. More preferably, the temperatures from the laminar flow element to the laminar flow element are set to 270℃~275℃ and 260~265℃, respectively.
[0020] After passing through the laminar flow element, the melt enters the die head, and the temperature of the die head is raised above the melting point. The die head temperature is set to 275~290℃, preferably 275~285℃; more preferably, the die head temperature is set to 280~285℃.
[0021] S2, Casting: The melt flows through the die lip to the casting roll to form a casting sheet. The temperature of the casting roll is 30~40℃, the contact position between the die lip and the casting roll is 2.5~5mm, and the width shrinkage of the casting sheet is 3~6%.
[0022] S3. Longitudinal stretching: The casting sheet is stretched longitudinally. During longitudinal stretching, the temperature of the preheating roller is 75~95℃ and the temperature of the stretching roller is 85~100℃. After preheating, it is stretched longitudinally with a stretching ratio of 2.5~4 times. Then it is cooled with a cooling roller temperature of 20~40℃.
[0023] S4. Lateral stretching: The sheet after longitudinal stretching is then stretched laterally. During lateral stretching, the preheating temperature is 100~130℃, the lateral stretching temperature is 120~145℃, and the lateral stretching time is 5~15s. The lateral stretching ratio is 3.5~5 times. The high-temperature setting temperature is 200~240℃, and the high-temperature setting time is 12~25s. The low-temperature setting temperature is 100℃~175℃, and the low-temperature setting time is 5~10s. After heat setting, the sheet is cooled at a temperature of 30~50℃ for 5~10s.
[0024] Polyester chips include polyester masterbatch and polyester base material. The polyester masterbatch includes opener flake particles with affinity for polyester and PET. The polyester masterbatch is obtained by co-extrusion granulation of opener flake particles with affinity for polyester and PET.
[0025] The opening agent flake particles are one or a combination of several of the following: flake calcium aluminate, graphene oxide, reduced graphene oxide, silanized graphene, and TiO2 / graphene composite. Preferably, the opening agent flake particles are one or a combination of several of the following: reduced graphene oxide, silanized graphene, and TiO2 / graphene composite.
[0026] The length and width of the opening agent flake particles are 100~5000nm and the thickness is 10~500nm. Preferably, the length and width of the opening agent flake particles are 500~3000nm and the thickness is 10~200nm. More preferably, the length and width of the opening agent flake particles are 1000~2000nm and the thickness is 10~50nm.
[0027] The proportion of the opening agent flake particles in the polyester masterbatch is 100~10000ppm, preferably 1000~10000ppm, and more preferably 3000~5000ppm.
[0028] The amount of polyester masterbatch added is 1% to 20% of the total amount of polyester chips. Preferably, the amount of polyester masterbatch added is 3% to 15% of the total amount of polyester chips. More preferably, the amount of polyester masterbatch added is 5% to 10% of the total amount of polyester chips.
[0029] like Figure 1-3 As shown, in step S1, the melt extrusion equipment has a feeding channel 1 and an extruder. The feeding channel 1 is located at the feed inlet of the extruder. The extruder includes a melting chamber, a metering pump 2, a melt pump 3, a filter 5, a melt pipe 6, and a die head 7. The melting chamber is connected to the metering pump 2, the metering pump 2 is connected to the melt pump 3, and a discharge valve 4 is provided between the melt pump 3 and the filter 5. The outlet end of the filter 5 is connected to the inside of the melt pipe 6.
[0030] The melt pipe 6 has a pipe wall 8 and a laminar flow element 9. The laminar flow element 9 is located inside the melt pipe 6 and is positioned near the outlet end of the melt pipe 6. The melt pipe 6 is divided into a front section and a rear section. The front section does not have the laminar flow element 9, while the rear section does. The laminar flow element 9 has three plate-shaped structural members arranged in parallel vertically. The three plate-shaped structural members are horizontally arranged and evenly spaced. The two sides of the plate-shaped structural members are welded to the pipe wall 8. The outlet end of the melt pipe 6 is connected to the die head 7.
[0031] The roughness Ra of the pipe wall should be sufficiently small, with a value of 10~1000 nm, to promote melt flow. Preferably, the roughness Ra of the pipe wall is 10~100 nm. The roughness Ra of the laminar flow element should be moderate. If it is too small, the parallel shear of the opening agent flake particles will be insufficient, and if it is too large, it will easily cause melt stagnation. Its Ra value is 100~2000 nm. Preferably, the roughness Ra of the laminar flow element is 100~500 nm.
[0032] The process of melt extrusion equipment for producing optical base film from polyester chips is as follows: The mixed polyester masterbatch and polyester base material are fed into the melt chamber of the extruder through the feeding channel 1 for melting and plasticization. The raw materials are accurately metered and transported by the metering pump 2, and then further propelled forward by the melt pump 3. The raw materials pass through the discharge valve 4 and enter the filter 5. After the impurities in the raw material melt are filtered out by the filter 5, the melt enters the melt pipe 6. In the latter half of the melt pipe 6, the opening agent flake particles are encased in the polyester masterbatch. The melt passes through the laminar flow element 9 and is subjected to strong parallel shear force under a specific temperature gradient. The opening agent flake particles are stacked along the thickness direction and arranged horizontally layer by layer along the direction of travel. Then, they enter the die head 7 and are extruded and formed. The opening agent flake particles are neatly arranged horizontally in the melt, thus arranging horizontally on the surface of the optical base film, resulting in excellent surface smoothness of the optical base film and solving the "orange peel" problem. The high affinity of the opening agent flake particles to polyester also makes them evenly dispersed and less agglomerated, further improving the microscopic smoothness. Example:
[0033] Preparation of polyester masterbatch: Silane graphene with a length and width of 1000 nm and a thickness of 10 nm was selected and granulated by extrusion using a twin-screw extruder with a ratio of 0.3% silane graphene and 99.7% polyester PET.
[0034] Preparation of optical base films for polarizers: S1. Ingredient Drying: Mix 5% polyester masterbatch and 95% polyester base material, and dry at above 150°C for at least 4 hours.
[0035] S2. Extrusion: The mixture of polyester masterbatch and polyester base material is melted and extruded. The melt passes through metering pump 2 at 270°C, discharge valve 4 at 275°C, filter 5 at 275°C, and enters melt pipe 6. The temperature reaches 270°C before laminar flow element 9 in melt pipe 6, drops to 260°C at laminar flow element, and flows out through die head at 280°C after passing through laminar flow element 9. The roughness of laminar flow element 9 is 100nm, and the roughness of pipe wall 8 is 10nm.
[0036] S3, Casting sheet: After the melt flows down 2.5mm at the die lip, it adheres to the cooling drum at 30℃ to form a casting sheet, and the width shrinkage of the casting sheet is 3%.
[0037] S4. Longitudinal stretching: The cast sheet is gradually heated by the preheating rollers, with a temperature gradient of 75~85℃. The stretching rollers are at 85℃, and the stretching ratio is 2.5 times. It is then cooled into a unidirectional sheet by the cooling rollers at 20℃.
[0038] S5. Lateral Stretching: In the lateral stretching machine, the unidirectional sheet first passes through the preheating section, where it is heated in stages using electric and steam heating at a rate of 15℃ / min. The temperature gradient in the preheating section is 100℃~115℃. The unidirectional sheet then enters the lateral stretching section, which uses electric heating with a temperature range of 120~135℃. The unidirectional sheet is clamped by chain clamps and stretched by 350% to form a biaxially stretched film. The lateral stretching time is 5 seconds. The biaxially stretched film then enters the high-temperature setting section for high-temperature setting, using electric heating with a temperature range of 200~225℃ and a setting time of 12 seconds. Next, the biaxially stretched film enters the low-temperature setting section, also using electric heating with a temperature range of 100~150℃ and a setting time of 5 seconds. Finally, the biaxially stretched film enters the heat-setting cooling section, where it is cooled at 30℃ for 5 seconds.
[0039] Three identical full-width film samples A, B, and C obtained through Example 1 were selected for roughness inspection, agglomeration inspection, and visual "orange peel" inspection, respectively. The test results are shown in Table 1.
[0040] Roughness inspection: The Mahr Marsurf M 300C roughness tester was used to test the Ra and Rmax of the sample at 25℃. Five sets of tests were conducted for each sample and the average value was taken.
[0041] Aggregate test: The sample to be tested was magnified 1200 times under a 3D microscope (VK-X1050, Keyence), and the size and height of visible particles were randomly read. At least 10 sets of data were read, and the mean and range were calculated.
[0042] Visual inspection of "orange peel": Visually inspect the sample under fluorescent light. Clearly visible "orange peel" texture is marked as ○, slight "orange peel" texture as ◇, and no "orange peel" texture as ☆.
[0043] Table 1. Microscopic smoothness test results of the three sets of full-width thin films obtained in Example 1: . Example
[0044] Preparation of polyester masterbatch: Silane graphene with a length and width of 1500 nm and a thickness of 20 nm was selected and granulated by extrusion using a twin-screw extruder at a ratio of 0.4% silane graphene and 99.6% polyester PET.
[0045] Preparation of optical base films for polarizers: S1. Ingredient Drying: Mix 7% polyester masterbatch and 93% polyester base material, and dry at above 150°C for at least 4 hours.
[0046] S2. Extrusion: The mixture of polyester masterbatch and polyester base material is melted and extruded. The melt passes through metering pump 2 at 280°C, discharge valve 4 at 285°C, filter 5 at 280°C, and enters melt pipe 6. The temperature reaches 275°C before laminar flow element 9 in melt pipe 6, drops to 262°C at laminar flow element 9, and flows out at die head 7 at 283°C after passing through laminar flow element 9. The roughness of laminar flow element 9 is 200nm, and the roughness of pipe wall 8 is 20nm.
[0047] S3, Casting sheet: After the melt flows down 4mm at the die lip, it adheres to the cooling drum at 35℃ to form a casting sheet, and the width shrinkage of the casting sheet is 4.5%.
[0048] S4. Longitudinal stretching: The cast sheet is gradually heated by the preheating rollers, with a temperature gradient of 80~87℃. The stretching rollers are at 90℃, and the stretching ratio is 3.1 times. It is then cooled into a unidirectional sheet by the cooling rollers at 30℃.
[0049] S5. Lateral Stretching: In the lateral stretching machine, the unidirectional sheet first passes through a preheating section, where it is heated in stages using both electric and steam heating at a rate of 15℃ / min. The temperature gradient in the preheating section is 105℃~120℃. The unidirectional sheet then enters the lateral stretching section, which uses electric heating with a temperature range of 125~140℃. The unidirectional sheet is clamped by chain clamps and stretched 380% to form a biaxially stretched film. The lateral stretching time is 6 seconds. The biaxially stretched film then enters a high-temperature setting section for high-temperature setting, using electric heating with a temperature range of 210~230℃ and a setting time of 16 seconds. Next, the biaxially stretched film enters a low-temperature setting section, also using electric heating with a temperature range of 120~160℃ and a setting time of 8 seconds. Finally, the biaxially stretched film enters a heat-setting cooling section, where it is cooled at 35℃ for 7 seconds.
[0050] Three identical full-width film samples A, B, and C obtained through Example 2 were selected for roughness inspection, agglomeration inspection, and visual "orange peel" inspection, respectively. The inspection methods were the same as in Example 1, and the test results are shown in Table 2.
[0051] Table 2. Microscopic smoothness test results of the three sets of full-width thin films obtained in Example 2: . Example
[0052] Preparation of polyester masterbatch: Silane graphene with a length and width of 2000 nm and a thickness of 50 nm was selected and granulated by extrusion using a twin-screw extruder at a ratio of 0.5% silane graphene and 99.5% polyester PET.
[0053] Preparation of optical base films for polarizers: S1. Ingredient Drying: Mix 10% polyester masterbatch and 90% polyester base material, and dry at above 150°C for at least 4 hours.
[0054] S2. Extrusion: The mixture of polyester masterbatch and polyester base material is melted and extruded. The melt passes through metering pump 2 at 285°C, discharge valve 4 at 280°C, filter 5 at 280°C, and enters melt pipe 6. The temperature reaches 275°C before laminar flow element 9 in melt pipe 6, drops to 265°C at laminar flow element 9, and flows out at die head 7 at 285°C after passing through laminar flow element 9. The roughness of laminar flow element 9 is 500nm, and the roughness of pipe wall 8 is 100nm.
[0055] S3, Casting sheet: After the melt flows down 5mm at the die lip, it adheres to the cooling drum at 40℃ to form a casting sheet, and the width shrinkage of the casting sheet is 6%.
[0056] S4. Longitudinal stretching: The cast sheet is gradually heated by the preheating roller, which is set with a temperature gradient of 85~95℃. The temperature of the stretching roller is 100℃, and the stretching ratio is 4 times. It is then cooled into a unidirectional sheet by the cooling roller at a temperature of 40℃.
[0057] S5. Lateral Stretching: In the lateral stretching machine, the unidirectional sheet first passes through a preheating section, where it is heated in stages using both electric and steam heating at a rate of 15℃ / min. The temperature gradient in the preheating section is 115℃~130℃. The unidirectional sheet then enters the lateral stretching section, which uses electric heating with a temperature range of 130~145℃. The unidirectional sheet is clamped by chain clamps and stretched by 500% to form a biaxially stretched film. The lateral stretching time is 15s. The biaxially stretched film then enters a high-temperature setting section for high-temperature setting, using electric heating with a temperature range of 220~240℃ and a setting time of 25s. Next, the biaxially stretched film enters a low-temperature setting section, also using electric heating with a temperature range of 140~175℃ and a setting time of 10s. Finally, the biaxially stretched film enters a heat-setting cooling section, where it is cooled at 50℃ for 10s.
[0058] Three identical full-width film samples A, B, and C obtained through Example 3 were selected for roughness inspection, agglomeration inspection, and visual "orange peel" inspection, respectively. The inspection methods were the same as in Example 1, and the test results are shown in Table 3.
[0059] Table 3. Microscopic smoothness test results of the three sets of full-width thin films obtained in Example 3:
[0060] As shown in Examples 1-3, using flake particles with affinity for polyester PET as an opening agent, and passing through a specially designed melt extrusion device, the flake particles of the opening agent are horizontally and uniformly dispersed in the polyester melt in a laminar flow state. The optical base film for polarizing film prepared meets the requirements of roughness Ra value ≤ 50nm and Rmax ≤ 600nm. The film surface has no orange peel texture, the flake particles of the opening agent are uniformly arranged and there are no agglomerates with size ≥ 50μm and height ≥ 5μm. The flake particles of the opening agent are uniformly dispersed and have few agglomerates. The finished product has excellent microscopic smoothness. The amount of flake particles added is small, and the preparation process of the optical base film for polarizing film is also relatively simple.
[0061] The foregoing has shown and described the basic principles and main features of the present invention, as well as its advantages. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an optical base film for polarizers with high microscopic flatness, characterized in that: Includes the following steps: S1. Extrusion: Polyester chips are extruded into shape using a melt extrusion device. The polyester chips are melted in the main melt chamber and auxiliary melt chamber of the melt extrusion device, and then flow out precisely and compounded through a filter and melt pipe at the die distribution block. The extrusion temperature is 250~295℃. In order to increase the transverse shear force of the sheet particles at the laminar flow element in the melt pipe, the temperature of the melt pipe is set to at least two temperature sections, including the temperature before the laminar flow element and the temperature at the laminar flow element. The temperature before the laminar flow element is higher, and the temperature at the laminar flow element is lower than the melting temperature. From the laminar flow element to the laminar flow element, the temperature is set to 270~285℃ and 250~270℃, respectively. After passing through the laminar flow element, the melt enters the die, and the temperature of the die is raised above the melting point. The die temperature is set to 275~290℃. S2, Casting: The melt flows through the die lip to the casting roll to form a casting sheet; S3. Longitudinal stretching: The casting sheet is stretched longitudinally. S4. Lateral stretching: The sheet that has been stretched longitudinally is then stretched laterally. The polyester chips include polyester masterbatch and polyester base material. The polyester masterbatch includes open-opening agent flake particles with affinity for polyester and PET. The polyester masterbatch is prepared by co-extrusion granulation of open-opening agent flake particles with affinity for polyester and PET. The opening agent flake particles are one or a combination of several of the following: flake calcium aluminate, graphene oxide, reduced graphene oxide, silane graphene, and TiO2 / graphene composite. The length and width of the opening agent flake particles are 100~5000nm, and the thickness is 10~500nm. The proportion of the opening agent flake particles in the polyester masterbatch is 100~10000ppm; The amount of polyester masterbatch added is 1% to 20% of the total amount of polyester chips.
2. The method for preparing an optical base film for a polarizer with high microscopic flatness according to claim 1, characterized in that: The opening agent flake particles are one or a combination of several of reduced graphene oxide, silane graphene, and TiO2 / graphene composite; the length and width of the opening agent flake particles are 500~3000nm, and the thickness is 10~200nm; the proportion of the opening agent flake particles in the polyester masterbatch is 1000~10000ppm. In step S1, the temperatures from the laminar flow element to the laminar flow element are set to 270~280℃ and 250~265℃ respectively; the die head temperature is set to 275~285℃. The amount of polyester masterbatch added is 3% to 15% of the total amount of polyester chips.
3. The method for preparing an optical substrate film for a polarizer with high microscopic flatness according to claim 1, characterized in that: The length and width of the opening agent flake particles are 1000~2000nm, and the thickness is 10~50nm; the proportion of the opening agent flake particles in the polyester masterbatch is 3000~5000ppm; In step S1, the temperatures from the laminar flow element to the laminar flow element are set to 270℃~275℃ and 260~265℃ respectively; the die head temperature is set to 280~285℃. The amount of polyester masterbatch added is 5% to 10% of the total amount of polyester chips.
4. The method for preparing an optical base film for a polarizer with high microscopic flatness according to claim 1, characterized in that: In step S2, the temperature of the casting roll is 30~40℃, the distance between the die lip and the contact position of the casting roll is 2.5~5mm, and the shrinkage of the casting width is 3~6%.
5. The method for preparing an optical base film for a polarizer with high microscopic flatness according to claim 1, characterized in that: In step S3, during longitudinal stretching, the temperature of the preheating roller is 75~95℃, the temperature of the stretching roller is 85~100℃, and after preheating, longitudinal stretching is performed with a longitudinal stretching ratio of 2.5~4 times. Then, cooling is performed with a cooling roller temperature of 20~40℃.
6. The method for preparing an optical base film for a polarizer with high microscopic flatness according to claim 1, characterized in that: In step S4, during transverse stretching, the preheating temperature is 100~130℃, the transverse stretching temperature is 120~145℃, after preheating, the transverse stretching time is 5~15s, the transverse stretching ratio is 3.5~5 times, the high-temperature setting temperature is 200~240℃, the high-temperature setting time is 12~25s, the low-temperature setting temperature is 100℃~175℃, the low-temperature setting time is 5~10s, after heat setting, the cooling temperature is 30~50℃, and the cooling time is 5~10s.
7. The method for preparing an optical base film for a polarizer with high microscopic flatness according to claim 1, characterized in that: In step S1, the melt extrusion equipment has a feeding channel and an extruder. The feeding channel is located at the feed inlet of the extruder. The extruder includes a melting chamber, a metering pump, a melt pump, a filter, a melt pipeline, and a die. The melting chamber is connected to the metering pump. The metering pump is connected to the melt pump. A discharge valve is provided between the melt pump and the filter. The outlet end of the filter is connected to the inside of the melt pipeline. The melt pipe has a pipe wall and a laminar flow element. The laminar flow element is located inside the melt pipe and is positioned near the outlet end of the melt pipe. The laminar flow element has three plate-shaped structural members arranged in parallel vertically. The three plate-shaped structural members are horizontally arranged and evenly spaced. The two sides of the plate-shaped structural members are welded to the pipe wall. The outlet end of the melt pipe is connected to the die head. The process of producing optical base film by melt extrusion of polyester chips using the melt extrusion equipment is as follows: The mixed polyester masterbatch and polyester base material are fed into the melt chamber of the extruder through the feeding channel for melting and plasticization. The raw materials are accurately metered and transported by the metering pump and then further propelled forward by the melt pump. The raw materials enter the filter through the discharge valve. After the filter removes impurities from the raw material melt, the melt enters the melt pipe. When passing through the laminar flow element in the latter half of the melt pipe, the opening agent flake particles are encapsulated in the polyester masterbatch. As the melt passes through the laminar flow element, it is subjected to strong parallel shear force under a specific temperature gradient. The opening agent flake particles stack along the thickness direction and are arranged horizontally layer by layer along the direction of travel. Then, it enters the die head and is extruded and formed. The opening agent flake particles are neatly arranged horizontally in the melt, thus forming a horizontal arrangement on the surface of the optical base film, resulting in high surface smoothness of the optical base film.
8. The method for preparing an optical base film for a polarizer with high microscopic flatness according to claim 7, characterized in that: The roughness Ra value of the pipe wall is 10~1000nm to promote melt flow; the roughness Ra value of the laminar flow element is 100~2000nm.
9. The method for preparing an optical base film for a polarizer with high microscopic flatness according to claim 7, characterized in that: The roughness Ra value of the pipe wall is 10~100nm; the roughness Ra value of the laminar flow element is 100~500nm.
Citation Information
Patent Citations
Polyester resin composition and polyester film using same
CN104583314A
Optical body including multilayer optical film and thin adhesive layer
CN110720062A
Optical biaxially oriented polyester basement membrane for panel display and preparation method thereof
CN102582180A
Ultrathin antistatic PET (polyethylene glycol terephthalate) film for capacitor and manufacturing mehtod of ultrathin antistatic PET film for capacitor
CN102744941A